2010
DOI: 10.14573/altex.2010.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Serum-free cell culture: the serum-free media interactive online database

Abstract: Prefacethe supplementation of basal culture media with animal serum of different origins is essential for cell growth, metabolism, and to stimulate proliferation ("mitogenic effect"). the sera used most widely are bovine sera of adult or newborn animals, or of fetal origin. Fetal bovine serum (FBS) is a cocktail of most of the factors required for cell attachment, growth and proliferation and is thus used as an almost universal growth supplement effective for most types of human and animal (including insect) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
232
0
28

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(273 citation statements)
references
References 62 publications
1
232
0
28
Order By: Relevance
“…Moreover, we observed that the addition of 20% of serum caused greater cell proliferation in the early days of culture, since a significant increase was observed in the number of cells after primary culture. In FBS composition, these are commonly found: transportation, adhesion proteins and enzymes, hormones, growth factors, cytokines, fatty acids, lipids, vitamins, carbohydrates, and nitrogen nonprotein source (Brunner et al 2010) and a larger amount of these substances favor greater cell proliferative activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we observed that the addition of 20% of serum caused greater cell proliferation in the early days of culture, since a significant increase was observed in the number of cells after primary culture. In FBS composition, these are commonly found: transportation, adhesion proteins and enzymes, hormones, growth factors, cytokines, fatty acids, lipids, vitamins, carbohydrates, and nitrogen nonprotein source (Brunner et al 2010) and a larger amount of these substances favor greater cell proliferative activity.…”
Section: Discussionmentioning
confidence: 99%
“…FBS has been used for more than a century as a cell culture additive for most cell types cultured in vitro [38,39]. It has been previously shown that differences in serum composition lead to statistical differences in experimental outcomes [40].…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantages of FBS, such as undefined composition or batch-to-batch variations, have been known for decades. Alternatives to FBS have been proposed and include options such as sera from other species, reduced serum media, chemically defined FBS or chemically defined serum-free media [38,39]. Using defined FBS would eliminate the necessity to test every new batch of FBS and would minimize experimental differences due to different FBS batches or types.…”
Section: Discussionmentioning
confidence: 99%
“…Os esforços para desenvolver um substituto são principalmente baseados em duas intenções. Por um lado, a coleta e a produção do SFB são dois fatores eticamente problemáticos, por isso uma substituição é necessária (BRUNNER et al, 2010;JOCHEMS et al, 2002;VAN DER VALK et al, 2004). Por outro lado, os campos de rápida expansão de célula in vitro, cultura de tecidos, engenharia biomédica e a terapia celular requerem definidas e seguras condições de cultura celular livre de componentes de origem animal (ATALA, 2007;VAN DER VALK et al, 2010).…”
Section: Lista De Ilustraçõesunclassified
“…Por outro lado, estratégias alternativas de expressão gênica têm surgido, algumas se utilizando de diferentes vírus para a produção de partículas semelhantes às partículas virais (TAN, 2006 Além disso, é conhecido por ser um suplemento quimicamente mal definido, tendo variações qualitativas e quantitativas que exibem uma possível fonte de contaminação microbiana como fungos, bactérias, vírus, micoplasma e príons, além de trazer dificuldades no processo de recuperação e purificação do bioproduto devido à presença de outras proteínas não interessantes (BRUNNER et al, 2010;GSTRAUNTHALER, 2003;VAN DER VALK et al, 2010 …”
Section: Lista De Ilustraçõesunclassified